Using surveillance and economic data to make informed decisions about rotavirus vaccine introduction. Issue 51 (14th December 2018) - Cohen, Adam L.; Aliabadi, Negar; Serhan, Fatima; Tate, Jacqueline E.; Zuber, Patrick; Parashar, Umesh D.
Highlights: Rotavirus vaccine is not used in many countries globally. Surveillance and economic data are key for rotavirus vaccine policy decisions. Countries should monitor rotavirus before and after vaccine is introduced. Countries should monitor rotavirus vaccine safety. Abstract: While rotavirus vaccines are available, safe, and effective, many countries are not yet widely using these vaccines. Surveillance for rotavirus disease and potential vaccine adverse events is critical for country decision making about rotavirus vaccine. This special issue shares rotavirus and intussusception disease surveillance data and rotavirus vaccine cost-effectiveness analyses from countries that have yet to introduce rotavirus vaccines into their routine infant immunization programs. The studies highlight the substantial burden of rotavirus disease and the cost-effectiveness of rotavirus vaccine in a broad set of countries without rotavirus vaccine in their routine immunization programs.